Studi Pengaruh Bentuk dan Kemiringan Permukaan Pilar Terhadap Kekuatan dan Faktor Keamanan Pilar - Rully Nurhasan Ramadani; Iswandaru Iswandaru; Ridho K. Wattimena; Made A Rai (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2019)
Study of stability and pillar failure mechanism with a variety of methods have beencarried with empirical and analytical approach. H. Moomivand dan V.S. Vutukuri in 2008 doto research with physical model of coal cubic with ratio of 0,25 to 10 with surface of pillar ishorizontal, this research aims to investigated changes in the ratio of pillar on compressivestrength and pillar mine failure mechanism, to study the relationship do the physical modellingwith 5 variations of height of 5 cm – 40 cm each pillar geometry has 7 variatons inclinedsurface 0o-30o. Samples of the pillar of testing with direction of the axial load on the body pillaruntil failure. Other than that do to 2D numerical modelling with finite element methods withassisted of software Phase2 (Rockscience). Physical modelling result showed the value ofthe compressive strength and the strength of pillar will be increased with the increasing ratioof pillars w/h. Effect of change in the inclined surface pillar to the compressive strength andpillar of strength showed no behavioral changes in the compressive strength and the strengthof the pillars to change the angle of the surface of the pillar. Changes in strength factor andsigma 1 showed decreasing of the value when the angle of the pillar is increasing eventhough the changes in the value of the numerical modeling results are not significant.